STARLINK ON COMPETITION OF INTERNET PROVIDERS IN INDONESIA: A BUSINESS LAW REVIEW - Hukunala, Sandy Victor (Notary Master Programe, Faculty of Law Universitas Jenderal Soedirman, 2024)
In Indonesia, the rapid growth of internet users highlights the need for wider access, especially in remote areas. The arrival of Starlink, a satellite project from SpaceX, offers a new solution with satellite technology that can reach areas that are difficult to reach by conventional cable infrastructure. This research explores the challenges and opportunities that conventional internet service providers face with the presence of Starlink. This research uses a normative legal research method with a statutory and conceptual approach. The results show that Starlink can improve internet access in remote areas but faces challenges in the aspects of regulation, competition and consumer protection. With the right approach, Starlink has the potential to support inclusive digital transformation in Indonesia.Keywords: Business Law; Internet; Starlink